Functional biodiversity of lipids in Antarctic zooplankton: Calanoides acutus, Calanus propinquus, Thysanoessa macrura and Euphausia crystallorophias - Falk-Petersen, Stig; Sargent, John R; Lønne, Ole Jørgen; Timofeev, Sergej (Polar Biology, 1999)
Zooplankton samples were collected in January 1993 off Dronning Maud Land along a transect from open waters to the marginal ice zone close to the Antarctic ice shelf. Thysanoessa macrura was caught in open waters while Calanoides acutus and Calanus propinquus were mainly sampled between ice floes in the marginal ice zone. The “ice-krill”Euphausia crystallorophias was found over the shelf directly associated with ice floes. T. macrura had a lipid content up to 36% of its dry weight with the dominant lipid class, wax ester, accounting for 45–50% of the total lipid. The predominance of 18:1 fatty alcohols is the striking characteristic of the wax esters. Small specimens of E. crystallorophias had lipid levels up to 26% of their dry weight with, unexpectedly, triacylglycerols being the dominant lipid (up to 41% of total lipid). The small levels of wax esters in these animals (3–6% of total lipid) had phytol as a major constituent. Large specimens of E. crystallorophias had up to 34% of their dry weight as lipid, with wax esters (47% of total lipid) dominated by 16:0 and 14:0 fatty alcohols as the major lipid. Calanus propinquus had lipid levels of up to 34% of their dry weight, with triacylglycerols (up to 63% of total lipid) being the dominant lipid. High levels of 22:1 (n-9) fatty acid were present in the triacylglycerols. Calanoides acutus had lipid levels up to 35% of the dry weight with wax esters accounting for up to 83% of total lipid. High levels of (n-3) polyunsaturated fatty acids were recorded with 20:5(n-3), 22:6(n-3) and 18:4(n-3) being the dominant moieties. On the basis of their lipid compositions we deduce that: (1) Calanoides acutus is the strictest herbivore among the four species studied, heavily utilizing the typical spring bloom; (2) T. macrura is essentially omnivorous, probably utilizing the less defined bloom situations found in oceanic waters; (3) E. crystallorophias is an omnivore well adapted to utilize both a bloom situation and to feed on ice algae and micro-zooplankton associated with the ice; (4) Calanus propinquus seems to be the most opportunistic feeder of the four species studied, probably grazing heavily on phytoplankton during a bloom and, during the rest of the year, feeding on whatever material is available, including particulates, flagellates and other ice-associated algae. We conclude that the different biochemical pathways generating large oil reserves of different compositions, enabling species to utilize different ecological niches, are major determinants of biodiversity in polar zooplankton.
Keywords: NARE 1992/93; Sørishavet; biodiversitet; biokjemi; dyreplankton; krill; lipider; marin biologi; zooplankton

Zooplankton in the marginal ice zone off Dronning Maud Land - population structure and trophic relationship - Falk-Petersen, Stig; Lønne, Ole Jørgen (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; alger; fytoplankton; krill; zooplankton

Antarctic krill Thysanoessa macrura fills a major gap in marine lipogenic pathways - Kattner, Gerhard; Hagen, Wilhelm; Falk-Petersen, Stig; Sargent, John R.; Henderson R. James (Marine Ecology Progress Series, 1996)
The unique predominance of oleyl alcohols (18:1) is the striking characteristic of the lipids of the Antarctic euphausiid Thysanoessa macrura. The 2 isomers 18:1(n-9) and 18:1(n-7) occurred in similar proportions in the wax esters of T. macrura and comprised up to 80% of the total fatty alcohols. The remainder consisted mostly of the 20:1(n-9) alcohol along with small amounts of the 22:1(n-11) alcohol. No marine zooplankton species has previously been reported which produces wax esters with significant amounts of 18 carbon fatty alcohols. T. macrura specimens were collected in the high Antarctic Weddell Sea during autumn 1992 and summer 1993. Their lipid levels were high, about 40 to 50% of the dry mass with up to 70% of the total lipid as wax esters. The wax ester fatty acids were dominated by the saturates 14:0 and 16:0, which, along with the monounsaturate 18:1(n-9), accounted for more than 80% of the total fatty acids. Phospholipids contained high levels of (n-3) polyunsaturated fatty acids (20:5 and 22:6) typical of membrane lipids from marine zooplankton. The precise significance of the unique wax ester composition in T. macrura is not clear but this discovery underscores the biochemical adaptability of Antarctic zooplankton species to a constantly cold and highly seasonal polar environment.
Keywords: Sørishavet; Weddellhavet; biokjemi; dyreplankton; hoppekreps; krill; marin biologi; zooplankton; økologi

The physiology of polar marine zooplankton - Clarke, Andrew; Peck, Lloyd S (Polar Research, 1991)
Keywords: Sørishavet; marin biologi; polarområdene; zooplankton

Microbial autotrophic and heterotrophic eucaryotes in Antarctic waters: relationships between biomass and chlorophyll, adenosine triphosphate and particulate organic carbon - Hewes, Christopher D.; Sakshaug, Egil; Reid, Freda M. H.; Holm-Hansen, Osmund (Marine Ecology Progress Series, 1990)
Microscopical examination of near-surface eucaryotic microbial populations in circumcontinental waters of Antarctica indicated that nanoplankton (<20 μm diameter) dominated in regions with low chlorophyll concentrations (< 1 μg l⁻¹). About 30 % of the mean nanoplankton carbon consisted of heterotrophic flagellates. Heterotrophic microplankton carbon (> 20 μm diameter) was generally less significant. The variation in phytoplankton biomass was the result primarily of changes in cell density of pennate diatoms in the East Wind Drift, and of centric diatoms in the Weddell Sea and the Scotia Ridge region. Autotrophic and heterotrophic carbon as determined by microscopical analysis were compared with data for total particulate carbon, chlorophyll a, and adenosine triphosphate. Estimates for the C:chl ratio of autotrophs increased with decreasing concentrations of chlorophyll a, with mean values of 46 in bloom waters and 144 in 'blue water'. A C:ATP ratio for heterotrophic nanoplankton was estimated to be about 100, while that for heterotrophic microplankton may be lower. Algorithms, incorporating concentrations of chlorophyll a and ATP, are described which allow estimates of autotrophic and heterotrophic microbial biomass.
Publisher: Inter-Research Science Center
Keywords: Sørishavet; alger; biomasse; fytoplankton; marin biologi; oseanografi; plankton; zooplankton